Factors influencing consumer purchasing behaviour towards online food delivery services - Md Jusoh, Zuroni; Rahiman, Nurnazrenatasah; Saworo, Siti Norizazi Wanani (Malaysian Consumer and Family Economics Association, 2021)
This research aims to identify factors influencing consumer purchasing behaviour towards online food delivery services. A total of 384 respondents from different zones in Peninsular Malaysia known as Southern Zone (Johor Bharu), Northern Zone (Pulau Pinang), Central Zone (Shah Alam) and Eastern Zone (Kuala Terengganu) were involved in this research—selected through multistage random sampling, simple random sampling for randomly selecting every state, cluster sampling for only focusing on the urban area, and convenient sampling focusing on the selected community. The data were collected through a questionnaire, and the results showed that consumer behaviour on purchasing online food delivery services was at a positive level. Multiple linear regression analysis found that the Adjusted !2 = 0.624 showed that taken as a set, the predictor factors of income, convenience, trustworthiness, various food choice, attitude, and intention for a 62.4 per cent variance of behaviour. The most significant predictor factors were attitude (Beta= 0.052) followed by intention (Beta= 0.050) and trustworthiness (Beta = 0.050). This research proved that Malaysia has a rapid growth of the online business that has strengthened the food industry. For future research, this study can be expanded to all states in Malaysia, including East Malaysia (Sabah & Sarawak), to form a larger sample size representing the whole of Malaysia, avoiding bias and increasing consumer behaviour research.